2020
DOI: 10.1002/smll.202006357
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Labeling Mediated Targeting and Thermal Killing of Gram‐Positive Bacteria by Self‐Reporting Janus Magnetic Nanoparticles

Abstract: Nanoparticles have been widely used in detection and killing of bacteria; however, targeting bacteria is still challenging. Delicate design of nanoparticles is required for simultaneous targeting, detection, and therapeutic functions. Here the use of Au/MnFe2O4 (Au/MFO) Janus nanoparticles to target Gram‐positive bacteria via metabolic labeling is reported and realize integrated self‐reporting and thermal killing of bacteria. In these nanoparticles, the Au component is functionalized with tetrazine to target t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 46 publications
(52 reference statements)
0
41
0
Order By: Relevance
“…[ 186 ] Most of these targets are based on the inherent structure of bacteria, which makes it difficult for the bacteria to develop drug resistance. [ 189 ] At the same time, targeting can enhance the affinity between bacteria and materials, which could achieve different antibacterial patterns such as active adsorption on bacteria and limiting bacterial migration; [ 190 ] 2) Unique physical forms (spiral, star, and spherical) of micro/nano robots endow them with a strong ability to tear biofilm. [ 187 ] The vast majority of micro–nano robots can be manipulated artificially to achieve long‐distance targeting for infected sites, which can be helpful for removing bacteria effectively for various medical equipment and implants.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…[ 186 ] Most of these targets are based on the inherent structure of bacteria, which makes it difficult for the bacteria to develop drug resistance. [ 189 ] At the same time, targeting can enhance the affinity between bacteria and materials, which could achieve different antibacterial patterns such as active adsorption on bacteria and limiting bacterial migration; [ 190 ] 2) Unique physical forms (spiral, star, and spherical) of micro/nano robots endow them with a strong ability to tear biofilm. [ 187 ] The vast majority of micro–nano robots can be manipulated artificially to achieve long‐distance targeting for infected sites, which can be helpful for removing bacteria effectively for various medical equipment and implants.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Thus far, numerous materials have been reported to inactivate microorganisms and viruses, such as metals [14][15][16] and organic materials [17][18][19][20] for virucidal applications, and molecules, [21][22][23][24][25] polymers, [26][27][28][29] and metals [30][31][32][33] for bactericidal applications. It was reported that metal nanoparticles, cationic polymers, or metal ions can interact strongly with negatively charged bacterial envelopes, providing them a highly efficient bactericidal capacity.…”
Section: Introductionmentioning
confidence: 99%
“…82,84 Metabolic labeling-based bio-orthogonal reactions have also been demonstrated to improve the targeting capability of therapeutic nanoparticles, enhancing the thermal killing efficiency for pathogenic bacteria. 29 By extending natural surface ligands to metabolic chemical analogs, diverse artificial ligands can be incorporated onto the bacterial surface without interfering with native biological processes, vastly expanding the capability for bacterial surface engineering.…”
Section: Artificial Surface Ligands and Interactionsmentioning
confidence: 99%
“…Many different functional materials, including fluorophores, 18,19 photosensitizers, 20,21 polymers, 22,23 biomolecules (unnatural sugars, 24 unnatural amino acids, 18,25 peptides, 26 proteins, 27 nucleic acids, 28 etc. ), nanoparticles, 29,30 as well as extruded cell membranes, 31,32 have been incorporated onto the bacterial surface. These artificial functions have enabled a better understanding of natural interactions and realized a wide range of applications including pathogen detection, 33 cell-based therapeutics, 20 and multicellular assembly.…”
Section: Introductionmentioning
confidence: 99%